ENHANCING COMMUNITY RELIGIOSITY THROUGH EFFECTIVE RELIGIOUS OUTREACH: Optimizing Da'wah Strategies of Majelis Ulama Indonesia (MUI) in Sintang - Lutfiyah, Umi 'Adilah (Jurnal Dakwah, 2023)
Da'wah is an inviting activity carried out by da'i to mad'u. The Majelis Ulama Indonesia (MUI) of Sintang Regency has implemented a da'wah strategy deeply rooted in the philosophy of da'wah to enhance community religiosity, particularly during the COVID-19 pandemic. In fulfilling its role as a guiding organization aimed at nurturing a generation with noble character, MUI Sintang collaborates with Radio Republik Indonesia (RRI) to broadcast its da'wah messages. Radio is chosen as a medium because it is accessible to all segments of society, especially in rural areas where other forms of communication may be limited due to poor signal reception. The da'wah efforts by MUI Sintang are carefully designed to ensure that every element of the da'wah process is considered, with the ultimate goal of making the da'wah message acceptable, understandable, and impactful in changing the thoughts and behaviors of the mad'u. This study explores the effectiveness of these strategies and their role in enhancing the religiosity of the community in Sintang Regency.